2015
DOI: 10.1177/2168479015586001
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Based Monitoring: A Closer Statistical Look at Source Document Verification, Queries, Study Size Effects, and Data Quality

Abstract: It is recommended that SDV, rather than just focusing on key primary efficacy and safety outcomes, focus on data clarification queries as highly discrepant (and the riskiest) data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 8 publications
1
23
0
2
Order By: Relevance
“…However, there is mounting evidence that SDV is far less useful than originally thought 1À5 and can be reduced by >90% (and altogether eliminated for large studies) without any measurable impact on data quality. 6 The vast majority of data errors identified through SDV are random in nature and evenly distributed across sites and treatment groups and can be caught using standard edit checks and statistical approaches. 6 Indeed, a recent analysis of site monitoring reports revealed that centralized monitoring activities could have identified 95% of the findings of on-site monitoring visits, <1% of which were critical or major in nature.…”
Section: T a G G E D H 1 Introductiont A G G E D E N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is mounting evidence that SDV is far less useful than originally thought 1À5 and can be reduced by >90% (and altogether eliminated for large studies) without any measurable impact on data quality. 6 The vast majority of data errors identified through SDV are random in nature and evenly distributed across sites and treatment groups and can be caught using standard edit checks and statistical approaches. 6 Indeed, a recent analysis of site monitoring reports revealed that centralized monitoring activities could have identified 95% of the findings of on-site monitoring visits, <1% of which were critical or major in nature.…”
Section: T a G G E D H 1 Introductiont A G G E D E N Dmentioning
confidence: 99%
“…6 The vast majority of data errors identified through SDV are random in nature and evenly distributed across sites and treatment groups and can be caught using standard edit checks and statistical approaches. 6 Indeed, a recent analysis of site monitoring reports revealed that centralized monitoring activities could have identified 95% of the findings of on-site monitoring visits, <1% of which were critical or major in nature. 7 These observations have led regulatory agencies and industry consortia, such as TransCelerate, to embrace a risk-based monitoring (RBM) methodology that combines centralized and off-site review of important study parameters with an adaptive on-site monitoring approach that places greater emphasis on risk-mitigation activities, such as Good Clinical Practice, source data review (SDR) and training.…”
Section: T a G G E D H 1 Introductiont A G G E D E N Dmentioning
confidence: 99%
“…тість і в той же час має «сумнівні переваги» [13]. Справа в тому, що зовсім не обов'язково розробляти систему якості для кожної можливої помилки або на 100 % вручну виконувати перегляд всіх даних, тому що «завжди існуватимуть помилки, які непомітно прослизнуть через процес перевірки якості» [13,14]. Тому ключовим завданням є не підвищення візитів монітора до МПВ та 100 % SDV, а мінімізація впливу помилок у даних на остаточний результат клінічного дослідження.…”
Section: Issn 2311-1127unclassified
“…ЧАСТИН ЗАГАЛЬНОЇ ПРОБЛЕМИ Раніше було визначено, що використання електронної індивідуальної реєстраційної форми (еІРФ) у практиці клінічних досліджень дозволяє завчасно усунути можливі помилки, проводити постійний дистанційний моніторинг з боку спонсора/КДО та уповноважених осіб МПВ [2,14]. За даними деяких джерел такий спосіб контролю якості роботи з даними у клінічному випробуванні та дослідженнях біоеквівалентності є в 15 разів ефективнішим за ручне SDV [13]. Потреба уникнути потенційних порушень, підвищити ефективність прийняття рішень та забезпечення дослідників потрібною інформацією для прийняття правильних рішень актуалізує створення єдиної електронної бази даних добровольців та запровадження еІРФ для здорових добровольців, які беруть участь у клінічних дослідженнях.…”
Section: виділення не вирішених ранішеunclassified
“…A recent query to all UK Clinical Research Collaboration (UKCRC), registered Clinical Trials Units (CTUs) revealed that many units routinely collect and report data for each site in a trial; such as numbers randomised, case report forms (CRFs) returned, data quality, missing primary outcome data, and serious breaches. How such data are used to assess and manage performance varies widely however [37]. Agreeing a small number of metrics for site performance that could be easily collected, presented and monitored in a standardised way by a trial manager or trial co-ordinator would be a potentially useful tool to improve efficient trial conduct.…”
Section: Introductionmentioning
confidence: 99%